Governance, policing and human rights - Dhar, T.N. (2000)
Providing the backdrop of traditional values of governance in India, the author focuses on police as the major tool of governance. He first discusses widening role and functions of police, measures needed to enhance police effectiveness and accountability at professional level to improve police's public perception; followed by the need to improve situation regarding administration of criminal justice; and the present scenario of human rights in India highlighting problems being faced in enforcing human rights. Before concluding, he prescribes a list of suggestions to be carried out, which, according to him, can bring about significant change. - Reproduced
Keywords: Human rights; Police